Analisis Normatif Aspek Yuridis Tindak Pidana Perbankan Sebagai Bentuk Kejahatan Ekonomi - Sari, Sintia Aprilia; Fardiansyah, Ahmad Irzal; Tamza, Fristia Berdian (Universitas Sang Bumi Ruwa Jurai, 2025)
Banking crime is a form of white-collar crime that has a broad impact on the stability of the financial system and public trust. This research method uses a normative juridical approach. The sources and types of data used are primary and secondary. Data collection was conducted through library research. Data processing was carried out by selecting and examining the obtained data for completeness, as well as systematically classifying or grouping the data. Data analysis used qualitative juridical methods. This research focuses on the provisions of Law Number 10 of 1998 concerning Banking, Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering, and regulations of the Financial Services Authority (OJK). The results of this study indicate that banking crimes not only result in financial losses but also lead to a crisis of public trust. Therefore, strengthening regulations, increasing the role of law enforcement officials, and implementing prudential banking principles in banking practices are necessary.